The Application of Trigonometry in Ship Navigation Direction Determination to Improve Sailing Accuracy - Diana Ayu Wulandari; Abdurohman; Syahron Al Rosyid (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2026)
This article examines the use of trigonometry in determining ship navigation direction to improve sailing accuracy. The main problem discussed is route deviation caused by inaccurate bearing interpretation, current, wind, and limited manual verification of electronic navigation data. The research used a descriptive qualitative method through literature study and mathematical simulation. Data were analyzed with right-triangle relationships, arctangent, bearing conversion, distance estimation, and simple course-correction procedures. The simulations show that trigonometry helps navigators calculate heading direction, direct distance, lateral deviation, estimated arrival time, and correction angle. A movement of 30 km east and 40 km north produces a bearing of 36.87 degrees with a direct distance of 50 km. A 5 km eastward deviation during a 60 km northward track requires a 4.76 degree correction to the west. The novelty of this article lies in presenting trigonometry as a contextual bridge between mathematical concepts and practical maritime decision making. The implication is that trigonometric literacy supports safer, more efficient, and more accurate navigation, especially when electronic systems need to be checked manually.